A presença econômica chinesa na região da América Latina e Caribe e no Brasil: diplomacia, comércio e investimentos - Pera, Marina Pisati (2023)
China has gone from being a net recipient to a net issuer of Foreign Direct Investment (FDI) in the 21st century, as a result of a rapid process of economic and productive growth. Even though the Latin America and the Caribbean (LAC) region is not the main one in China's investment portfolio, the increase in IED, as well as in the flow of imports and exports, guarantees these countries a strategic place in the internationalization plan of Chinese companies, which has been underway since the economic reforms of 1978. FDI and trade flows show that LAC countries are primarily producers and exporters of commodities to China. High economic growth rates and continuous access to and supply of natural resources, especially food and energy, provide legitimacy and stability to the Chinese regime. In this context, LAC countries gain relevance for China's specific foreign policy objectives: securing the supply of commodities to guarantee the continuity of the regime. China's domestic and external political and economic objectives are intertwined - a pattern that is confirmed in its ties with the LAC region and with Brazil, the largest recipient of FDI in the region. However, since 2010, the Chinese government has diversified the sectors receiving investment in the region due mainly to domestic economic factors - among them, the economic slowdown that hit China as a consequence of the 2008 global financial crisis. Since the beginning of the 21st century, therefore, China's economic presence in the LAC region reflects domestic and international processes of China as an emerging global power